A quartz-based micro catalytic methane sensor by high resolution screen printing. (14th January 2016) - Lu, Wenshuai; Jing, Gaoshan; Bian, Xiaomeng; Yu, Hongyan; Cui, Tianhong
Abstract: A micro catalytic methane sensor was proposed and fabricated on a bulk fused quartz substrate using a high resolution screen printing technique for the first time, with reduced power consumption and optimized sensitivity. The sensor was designed by the finite element method and quartz was chosen as the substrate material and alumina support with optimized dimensions. Fabrication of the sensor consisted of two MEMS processes, lift-off and high resolution screen printing, with the advantages of high yield and uniformity. When the sensor's regional working temperature changes from 250 °C to 470 °C, its sensitivity increases, as well as the power consumption. The highest sensitivity can reach 1.52 mV/% CH4 . A temperature of 300 °C was chosen as the optimized working temperature, and the sensor's sensitivity, power consumption, nonlinearity and response time are 0.77 mV/% CH4, 415 mW, 2.6%, and 35 s, respectively. This simple, but highly uniform fabrication process and the reliable performance of this sensor may lead to wide applications for methane detection.